History lessons for students of the race of Law - Huertas Vallejos, Lorenzo (2021)
Lawyers and lawyers give little importance to studies of history, but history is talking about people who are governed by laws. So the question What types of law Peruvian was in the long historical process? Recall the early embryonic forms of government that is the Behetría and after the Archaic development and the pursuit of government best suited to the new social organizations profiles. Forms of customary law with permanent customs that determine the time of initiation of the person say: birth, puberty, marriage How to behave when Phoenicia society an individual? What are the necessary rituals for the spirits reach places where gods dwelled creators, or where they remained the spirits of people who had respected and complied with ethnic codes? What were the levels of customary law in Peru? What kind of State and Law was in time of the Incas? Were there any written law? How were and are laws in a theocratic government, when the controls being the product of a divine emanation believed? What message containing historical Quipus the same as the quellcas? How were the laws that empires of old data as happened in China were issued? or short data empires as the Inca?